Evaluation of urinary acidification in children: Clinical utility - Díaz-Anadón, Lucas; Cardo, Leire; Santos, Fernando; Gil-Peña, Helena (Frontiers in Pediatrics, 2022)
The kidney plays a fundamental role in acid-base homeostasis by reabsorbing the filtered bicarbonate and by generating new bicarbonate consumed in the buffering of non-volatile acids, a process that leads to the acidification of urine and the excretion of ammonium (NH4+). Therefore, urine pH (UpH) and urine NH4+ (UNH4+) are valuable parameters to assess urinary acidification. The adaptation of automated plasma NH4+ quantification methods to measure UNH4+ has proven to be an accurate and feasible technique, with diverse potential indications in clinical practice. Recently, reference values for spot urine NH4+/creatinine ratio in children have been published. UpH and UNH4+, aside from their classical application in the study of metabolic acidosis, have shown to be useful in the identification of incomplete distal renal tubular acidosis (dRTA), an acidification disorder, without overt metabolic acidosis, extensively described in adults, and barely known in children, in whom it has been found associated to hypocitraturia, congenital kidney abnormalities and growth impairment. In addition, a low UNH4+ in chronic kidney disease (CKD) is a risk factor for glomerular filtration decay and mortality in adults, even in the absence of overt metabolic acidosis. We here emphasize on the need of measuring UpH and UNH4+ in pediatric population, establishing reference values as well as exploring their application in metabolic acidosis, CKD and disorders associated with incomplete dRTA, including growth retardation of unknown cause.